A world recast : an American moment in a post-Western order - Serfaty, Simon (Rowman & Littlefield Publishers, 2012)
In this powerful and provocative book, distinguished scholar Simon Serfaty vigorously argues that while it is possible, and even desirable, to acknowledge the passing of the Western era, it is exaggerated to present it as an irreversible decline of the United States and the rest of the West, relative to China and the rest of the Rest. Rather, he shows that the unfolding post-Western moment of zero-polarity will be messy, involving a dozen or more other countries. But Serfaty convincingly contends that even during this moment of geopolitical transition, American power remains superior, and thus.